Trabalho de base: experiências e memórias de militantes políticos durante a ditadura militar no Brasil e atuação pós-ditadura - Ikedo, Fernanda (2023)
This dissertation presents narratives from political activists about the groundwork during the military dictatorship (1964-1985), as well as their actions after that period. The objective is, based on these experiences and memories, to rescue and analyze the narratives and reflections of the interviewees and the interviewee seeking to understand these political subjects in their formation, action, and historical context. We use Oral History as a methodology for sensitive listening (Rovai, 2021) and the transcreative act after the journey (MEIHY, SEAWRIGHT, 2021). The interviewees heard here - Celeste Fon, Pedro Pontual, Ranulfo Peloso and, Carlos Alberto Libânio Christo, Frei Betto - faced the military dictatorship and actively participated in the country's re-democratization process, acting with the formation-organization-action tripod through popular education as a pedagogy to do the essential work. The theoretical, interdisciplinary foundation brings the concepts of experience and memory. It discusses the categories brought up by the narratives, such as political formation, amnesty, social struggle, and criticism of removing the bases with a focus on political institutionality.